Influence of Play Approach Against Sprint Learning Outcomes - Devi Catur Winata; Muhammad Fahmi; Andi Nur Abady (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2020)
In general, the purpose of this study was to improve the results of sprinting learning in physical education learning by using the application of the play approach for grade VII students of SMP Negeri 6 Kisaran. This study uses an experimental study. The subjects in this study were students of class VII SMP Negeri 6 Kisaran city. This research was conducted with six meetings the results of the average value of students in learning sprint 70 or 60% of students completed, and 40% of students who did not complete. In the second phase which was realized through the actions of the results of reflection from the pre test, the results were an average of 80 or 88% of students completed and 12.5% ​​of students who did not complete. Based on the results of the study it can be concluded that: (1) With the approach to playing sprint running learning outcomes increase, (2) With the application of the play approach applied through the game helps students improve the learning outcomes of sprint running.